2014
DOI: 10.1063/1.4865798
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure effects on shock-induced surface jetting

Abstract: Articles you may be interested inIntegrated experimental and computational studies of deformation of single crystal copper at high strain ratesThe interface and surface effects of the bicrystal nanowires on their mechanical behaviors under uniaxial stretching

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 37 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…To our knowledge, only recent MD simulations performed on atomistic systems allowed to provide directly from computations ejecta size distributions [25][26][27]. Particulate computations are indeed at the good scale to provide information on the microscopic mechanisms of plastic deformation and/or fragmentation of metals under melting or release melting conditions [25][26][27][28][29][30][31]. However, the main objection on these simulations is that the scales and times involved are smaller than those in real structures by at least 3 or 4 orders of magnitude; and in the absence of reliable data, it is effectively not yet possible to confirm the results with experiments or models.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only recent MD simulations performed on atomistic systems allowed to provide directly from computations ejecta size distributions [25][26][27]. Particulate computations are indeed at the good scale to provide information on the microscopic mechanisms of plastic deformation and/or fragmentation of metals under melting or release melting conditions [25][26][27][28][29][30][31]. However, the main objection on these simulations is that the scales and times involved are smaller than those in real structures by at least 3 or 4 orders of magnitude; and in the absence of reliable data, it is effectively not yet possible to confirm the results with experiments or models.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the v x for the jet head region is higher than in the other part, giving rise to two competing phenomena: the mass accumulation in the head and necking behind it. 51 The decrease in their velocity gradients then reduces the mass accumulation and accelerates the necking at later times, which causes the subsequent fragmentation of a jet.…”
Section: Resultsmentioning
confidence: 99%
“…Further, simulations of ejecta formation from the nanometer to centimeter scales was also reported [42,47]. The effects of shapes of the surface perturbations on the surface perturbations was first reported in [6], but the 2010s also saw the shape of the perturbations on the ejecta source studied with molecular dynamics (MD) simulations [47,48].…”
Section: Smentioning
confidence: 99%